INTEGRASI ENERGI GELOMBANG LAUT PADA MATERI USAHA DAN ENERGI SERTA GETARAN HARMONIS SEDERHANA DALAM PEMBELAJARAN COOPERATIVE PROBLEM SOLVING - Marlisa Angriani; Ahmad Fauzi; Hamdi Rifai (Universitas Negeri Padang, 2015)
One of factor causes of low physics learning outcomes is the lack of students ability in problem solving. One of the solution to overcome this problem is to use the students worksheet integrated ocean wave energy with Cooperative Problem Solving learning model. The purpose of this research is to investigate the impact and contibution of the student worksheet integrated ocean wave energy to physics learning outcomes in Cooperative Problem Solving learning in XI grade SMAN 12 Padang. This research is Quasi Experimental Research with randomized control group only design. The population is the students of XI grade SMAN 12 Padang that listed in 2014/2015 academic year. Sampling techniques is cluster random sampling. Research data in the form of physics learning outcomes data and the score of student worksheet integrated ocean wave enegy data. Research instruments are written test (essay) for knowledge competence, observation sheet for attitude competence, and score rubric for skill competence. Based on the data analysis, can be concluded that there are significance effect and contribution student worksheet integrated ocean wave energy in Cooperative Problem Solving learning to the physics learning outcomes in XI grade SMAN 12 Padang